Ironie als interkultureller Stolperstein. Grass´ Beim Häuten der Zwiebel im Spiegel der italienischen Übersetzung - Pugliese, Rossella (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Literary irony is deceptive and can ’t be conveyed easily across cultures: due to the strongly cultural anchor, an originally ironic text does not necessarily have the same ironic impact when translated nor is it ironic to the same extent. On the basis of a comparison between the German original of Grass ’s Beim Häuten der Zwiebel and the Italian translation Sbucciando la cipolla this paper is aiming at investigating up to what point and with which tools and means it is possible to transfer irony as a linguistic convention with a strongly cultural dimension into a foreign language and how it could be elaborated and made suitable to a foreign cultural environment.